Clinical significance of unsuspected rise in cardiac troponin in the setting of falls in older people. Issue 6 (18th June 2010) - Maréchaux, Sylvestre; Lubret, Rémy; Delsart, Pascal; Hattabi, Medhi; Six-Carpentier, Marie-Michèle; Carpentier, Emilie; Coutant, Véronique; Pinçon, Claire; Le Tourneau, Thierry; Puisieux, François; Goldstein, Patrick; Asseman, Philippe; et al.
Abstract : Objectives: To assess the clinical significance of unsuspected rise in cardiac troponin I (cTnI) levels in elderly patients who have fallen. Design: Monocentre prospective observational pilot study Participants: Consecutive elderly patients (age >65 years) referred to the emergency department after being immobilised on the ground after a fall. Measurements: Clinical, laboratory and Doppler echocardiography data were collected on admission to assess the cardiac correlates of increased cTnI. The survival endpoint was a composite of death or cardiovascular event. Results: 60 patients were included in this study. Mean age was 81±8 years. Cardiac TnI was ≥0.05 ng/ml in at least one blood sample in 40 patients (67%). New diagnosis of cardiac disease was performed in 14 patients, 13 of them had cTnI ≥0.05 ng/ml. Transient apical ballooning was diagnosed in six patients. During a median follow-up of 92 (49–131) days death occurred in six patients, myocardial infarction in three, stroke in one and acute heart failure in five. Cardiac TnI ≥0.05 ng/ml was a predictor of these events (p=0.034). Conclusion: An unsuspected rise in cTnI correlates with new diagnosis of cardiac disease and is a potential marker of stress induced cardiomyopathy in elderly patients who fall. Cardiac TnI might be a strong predictor of outcome in these patients.